PUTTING THE HORSE BEFORE THE CART: A PRAGMATIST ANALYSIS OF KNOWLEDGE - Augusto, Luís M. (Faculdade de Filosofia e Ciências, 2011)
The de! nition of knowledge as justfied true belief is the best we presently have. However, the canonical tripartite analysis of knowledge does not do justice to it due to a Platonic conception of a priori truth that puts the cart before the horse. Within a pragmatic approach, I argue that by doing away with a priori truth, namely by submitting truth to justi! cation, and by accordingly altering the canonical analysis of knowledge, this is a fruitful de! nition. So fruitful indeed that it renders the Gettier counterexamples vacuous, allowing positive work in epistemology and related disciplines.